Organ Transplantation: A Life-Line or Death Row? - Anifowose, Oluwaseun Adeola; Oyelana, Oluwabori Ayobami (NIU Journal of Humanities, 2021)
This paper aims at an examination of organ transplantation with special focus on the viability or otherwise of transplantation as a life-saving procedure for patients with end-stage organ failures. It points out that the crucial issues in organ transplantation is centered on question of whether organ transplantation really serves the purpose of saving lives or a death-row and the question of how to ensure justice in the face of organ shortage. This paper therefore argues that organ transplantation which is supposed to serve solely the purpose of life saving is also a death row for those awaiting organs; this is because of the unavailability of organ, unwillingness to donate and the unfavorable role that the criteria for allocation does to others who are not opportune to have the needed organ before death. Keywords : Organ transplantation, life line, death row, justice, organ shortage,